2010
DOI: 10.1590/s0004-28032010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the immunohistochemical expressions of p53, bcl-2 and Ki-67 in colorectal adenocarcinoma and their correlations with the prognostic factors

Abstract: -Context -Search of tumors markers that allow treatment with higher survival rates, and indicate the response to treatment and recurrence of cancer -Objective -To analyze the immunoexpression of the proteins p53, bcl-2 and Ki-67 in colorectal adenocarcinoma and correlate them with the clinical-pathological prognostic factors. Method -Tissue microarray paraffin blocks were made from colorectal adenocarcinoma tissue resected from 82 patients who had undergone surgery but not chemotherapy or radiotherapy, at "Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
5
18
0
4
Order By: Relevance
“…Molecular markers can be useful factors in determining the disease progression, prognosis of patient's condition, and even response to treatments as well as selection of proper therapeutic methods (32). itive Ki67 expression in 62 tumoral samples and negative expressions in 20 other samples, indicating significantly high expression of this protein in CRC samples compared to normal colorectal tissues (33). Above-mentioned studies are consistent with the present study in terms of higher expression of Ki67 protein in colorectal adenocarcinoma samples compared to adenomatous and healthy specimens as well as its gradually increment in different phases of the diseases from the healthy tissue to adenomatous polyps and, ultimately, to colorectal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…Molecular markers can be useful factors in determining the disease progression, prognosis of patient's condition, and even response to treatments as well as selection of proper therapeutic methods (32). itive Ki67 expression in 62 tumoral samples and negative expressions in 20 other samples, indicating significantly high expression of this protein in CRC samples compared to normal colorectal tissues (33). Above-mentioned studies are consistent with the present study in terms of higher expression of Ki67 protein in colorectal adenocarcinoma samples compared to adenomatous and healthy specimens as well as its gradually increment in different phases of the diseases from the healthy tissue to adenomatous polyps and, ultimately, to colorectal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…In most of the human tumors a relation between Bcl-2 expression and survival has been shown (Yildirim et al, 2012). In studies searching Bcl-2 expression in colon cancer, expression rates were found between 31%-70% (Menezes et al, 2010). In our study; Bcl-2 expression rate was similar to these results.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, these data support the finding that when apoptosis is weak, a rapid progression of the disease may be observed (30). Like other published works (30,(35)(36)(37), no correlation between the status of studied proteins and response to treatment of patients was found in our study.…”
Section: Discussionsupporting
confidence: 73%